(untitled) (Journal of Medicine, 2011)
Renal involvement in lymphoma is not very uncommon but primary renal lymphoma is very rare and prognosis is poor. A 20 years male presented with localized, dull, constant pain and progressive swelling in left upper abdomen. He also gave history of significant weight loss. Examination findings revealed that he was anaemic, left kidney was hugely enlarged and hepatomegaly. Initially it seemed to be a case of renal cell carcinoma. But after doing invasive investigations it was proved to be a case of lymphoma, which considering all clinical and laboratory findings was diagnosed as a case of primary renal lymphoma. Keywords: Young man, Primary, Renal mass, Lymphoma DOI: http://dx.doi.org/10.3329/jom.v12i2.8424 JOM 2011; 12(2): 174-176